Jordan : 2010 Article IV Consultation-Staff Report and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2010)
The economy of Jordan was affected by the global crisis. Lower commodity prices helped improve Jordan's external position. Effective banking supervision has strengthened the capacity of Jordanian banks to withstand shocks. The authorities have implemented prudent fiscal and monetary policies. The medium-term fiscal strategy should be supported by a number of institutional reforms. The fixed exchange rate regime remains important for financial stability. Bank regulation and supervision should continue to focus on preventing excessive risk-taking.